2007
DOI: 10.1177/0883073807307976
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Sinus Thrombosis in Children: A Multicenter Cohort From the United States

Abstract: This study presents a large multicenter cohort of children with cerebral venous thrombosis from 5 centers in the United States and analyzes their clinical findings and risk factors. Seventy patients were included in the study (25 neonates, 35%). The age ranged from 6 days to 12 years. Thirty-eight (55%) were younger than 6 months of age, and 28 (40%) were male. Presenting features included seizures (59%), coma (30%), headache (18%), and motor weakness (21%). Common neurological findings included decreased leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
120
2
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 29 publications
(22 reference statements)
6
120
2
6
Order By: Relevance
“…Two other cases one with HbSC and one with HbSS were reported as part of a registry of 42 patients with DVST [5]. A third case was reported in registry of 63 patients from North America [8]. Two patients with sickle cell trait and DVST have also been reported [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other cases one with HbSC and one with HbSS were reported as part of a registry of 42 patients with DVST [5]. A third case was reported in registry of 63 patients from North America [8]. Two patients with sickle cell trait and DVST have also been reported [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Two patients with sickle cell trait and DVST have also been reported [9,10]. DVST is a rare disorder with an estimated annual incidence of 3-4 per million adults and up to 7 per million among children [8]. The incidence in patients with SCD is unknown as it has not been reported in the stroke trials of Cooperative Study of Sickle Cell Disease (CSSCD).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The most recent review of infants with CSVT found that 90% had predisposing factors identified (Table 2), with 16% of these patients having multiple risk factors. 26 The superior and lateral sinuses are the most frequently involved vessels. 86 Up to 30% of cases have reported venous infarction with subsequent hemorrhage.…”
Section: Venous Thrombosismentioning
confidence: 99%
“…The incidence of cerebral sinovenous thrombosis (CSVT) in childhood is estimated at 0.67 per 100 000 children per year with approximately half occurring in neonates. 25,26 Major presenting clinical features of CSVT include seizures, fever and lethargy. 25,26 The most recent review of infants with CSVT found that 90% had predisposing factors identified (Table 2), with 16% of these patients having multiple risk factors.…”
Section: Venous Thrombosismentioning
confidence: 99%
See 1 more Smart Citation